HUBUNGAN ANTARA PEMAHAMAN KONSEP SEHAT DENGAN KEBERSIHAN PRIBADI, KEPATUHAN BEROBAT SISWA KELAS V SD DI KECAMATAN GODEAN SLEMAN YOGYAKARTA - B Evi Suhartini (Jurnal Penelitian Humaniora, 2000)
Abstract Children’s concepts of health influence personal hygiene, prevention and treatment of illness. The aim of the research were to discover the relationship of understanding of health concepts and compliance behavior and children’s personal hygiene behavior. This research was a survey done from April to September 1998 in Godean, Sleman district, Yogyakarta. A questionnaire was used to collect data. Subject were 105 elementary school students in fifth grade, and were randomly selected. Product moment correlation with confidence of 0.05 was used for analyze the data. The result of the research showed that 1) There was  a positive significant relationship between understanding of health behavior, 2)positive relationship between the understanding of health concepts with behavior. Keywords: health concepts, personal hygiene, compliance behavior